L'accusa di magia e i cristiani nella tarda antichità - Marasco, Gabriele (Augustinianum, 2011)
It is generally held that in late antiquity the accusation of magic was used by Christians to attack the pagans. However, there is quite ample documentation to show that Christians themselves resorted to this, in doctrinal disputes, to strike at their respective adversaries, in particular the bishops and their principal collaborators. With such a charge, they not only aroused the fears of the masses, but also provoked the intervention of the imperial authorities, bringing about the removal and the exile of those condemned and even, in the case of Priscilian, their execution. The efficacy of this accusation was facilitated by a widespread faith and the terror of magic, but also by the ambiguity of the powers of the magician, which could be easily confused with the supernatural powers of a saint. In fact, the distinction depended on the source of those powers, respectively, demons and God.